Sleep Duration in Children and Its Influence on Glucose Homeostasis, Ingestive Behavior and Primary Examination Performance - , O. N. Ilochi; , A. N. Chuemere; , D. V. Dapper; , F. Saronee; , I. Ekwem (Archives of Current Research International, 2019)
Sleep is a natural periodic state of rest essential for normal psychophysiologic responses. This study revealed the influence of sleep on ingestive behavior, glucose homeostasis and primary examination performance. Six hundred children between 10 to 12 years of age were sampled. The study design included 4 groups, a to d, comprising 150 samples each. Sleep duration was 8pm to 6am, 10pm to 6am, 12am to 6am and 2am to 6am for groups a, b, c and d respectively. The results were collected after careful observation and scientific experimentation. Statistical analysis revealed values to be significantly different (P≤0.05) compared to group a. There was an inverse relationship between duration of sleep, quantity of food ingested and blood glucose level. As the duration of sleep was increased, there was a corresponding improvement in primary examination performance and blood glucose homeostasis. From the outcome of this study, sleep duration may influence ingestive behavior, blood glucose level and primary examination performance.